1987
DOI: 10.1021/jm00392a010
|View full text |Cite
|
Sign up to set email alerts
|

17-Heteroaroyl esters of corticosteroids. 2. 11.beta.-Hydroxy series

Abstract: The preparation and topical antiinflammatory potencies of a series of 17-furoyl and -thenoyl esters of 9 alpha-fluoro-11 beta-hydroxy-16 methyl and 9 alpha-chloro-11 beta-hydroxy-16-methyl corticosteroids are described. The 17 alpha-esters were introduced to the 9 alpha-fluoro 11-ketones or to the appropriate delta 9(11) compounds by direct acylation with the appropriate heteroaryl carbonyl chloride in the presence of 4-(dimethylamino)pyridine. Functionalization of the C ring was completed by standard methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The X-ray single crystal analysis agrees with the proposed structure and stereochemistry of the mometasone furoate molecule. 9 Bond lengths and bond angles are in the expected ranges. For the molecule structure, both forms have similar conformations.…”
Section: Resultsmentioning
confidence: 88%
“…The X-ray single crystal analysis agrees with the proposed structure and stereochemistry of the mometasone furoate molecule. 9 Bond lengths and bond angles are in the expected ranges. For the molecule structure, both forms have similar conformations.…”
Section: Resultsmentioning
confidence: 88%
“…In the past, clinical trials have shown that the antiinflammatory potential of MF is similar to triamcinolone [13,14] and stronger than the efficacy of betamethasone [9,10]. Therefore, MF was introduced as a member of the subgroup of glucocorticosteroids with high clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of new corticosteroids have been developed. Mometasone furoate (MF) has been introduced as a very potent corticosteroid associated with a low risk of systemic and topical side effects [9,10]. In the past, many clinical studies confirmed the efficacy in inflammatory skin diseases accompanied by low and rare adverse effects [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…topical corticosteroid [3] which has been shown to possess high anti-inflammatory activity and improved local and systemic tolerability [4][5].…”
Section: Introductionmentioning
confidence: 99%